2022
DOI: 10.3389/fcvm.2022.844876
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Performance of Sutureless vs. Conventional Bioprostheses for Aortic Valve Replacement: The 1-Year Core-Lab Results of the Randomized PERSIST-AVR Trial

Abstract: ObjectiveSutureless aortic valves are an effective option for aortic valve replacement (AVR) showing non-inferiority to standard stented aortic valves for major cardiovascular and cerebral events at 1-year. We report the 1-year hemodynamic performance of the sutureless prostheses compared with standard aortic valves, assessed by a dedicated echocardiographic core lab.MethodsPerceval Sutureless Implant vs. Standard Aortic Valve Replacement (PERSIST-AVR) is a prospective, randomized, adaptive, open-label trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…[9][10][11][12] However, whether sutureless valves are more advantageous than the conventional sutured prostheses for AVR is unclear. 7,[12][13][14][15][16][17][18] Therefore, this meta-analysis compared sutureless Perceval prostheses versus conventional sutured valves for AVR. The primary outcomes of interest were to compare the intraoperative variables (ACC and CPB times), valve's hemodynamic performance (postoperative peak and mean transvalvular pressure gradients, mean aortic valve area), length of stay (intensive care unit [ICU] and hospital stay), and the rate of postoperative pacemaker implantation and early mortality between the valves.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] However, whether sutureless valves are more advantageous than the conventional sutured prostheses for AVR is unclear. 7,[12][13][14][15][16][17][18] Therefore, this meta-analysis compared sutureless Perceval prostheses versus conventional sutured valves for AVR. The primary outcomes of interest were to compare the intraoperative variables (ACC and CPB times), valve's hemodynamic performance (postoperative peak and mean transvalvular pressure gradients, mean aortic valve area), length of stay (intensive care unit [ICU] and hospital stay), and the rate of postoperative pacemaker implantation and early mortality between the valves.…”
Section: Introductionmentioning
confidence: 99%
“… 20 A subanalysis of the Perceval Sutureless Implant Versus Standard-Aortic Valve Replacement (PERSIST-AVR) trial reported significantly reduced rates of major adverse cardiac and cerebrovascular events (MACCE), stroke, atrial fibrillation, and rehospitalization following SUAVR via ministernotomy as compared with conventional sutured AVR. 21 However, this did come at the expense of an increased permanent pacemaker implantation (PPI) rate. 22 Retrospective analysis of patients undergoing SUAVR via full sternotomy versus ministernotomy indicates equivalent intraoperative time parameters, reduced hospital and intensive care unit (ICU) length of stay (LOS), as well as reduced left ventricular diastolic volume with ministernotomy.…”
Section: Resultsmentioning
confidence: 99%
“…The was no significant difference in the rate of overall PVL for SUAVR and SAVR, respectively (11.3% vs 15.0%, P = 0.315). 21 In a subanalysis of the PERSIST-AVR trial comparing ministernotomy and full sternotomy approaches, SUAVR resulted in significantly lower MACCE (5.2% vs 10.8%), stroke (1.0% vs 5.4%), atrial fibrillation (4.2% vs 11.4%), and rehospitalization (21.8 vs 47.6 days) compared with SAVR when performed via ministernotomy; however, for SUAVR, this came at the expense of a higher PPI rate (11% vs 1.6%). 22 An additional subanalysis of this trial by Lorusso et al analyzed the influence of prosthesis size on PPI rates and determined that increased rates of PPI following SUAVR came only with implantation of the extra-large device.…”
Section: Resultsmentioning
confidence: 99%
“…Perceval sutureless AVRs have been effectively used in the treatment of aortic stenosis. [23][24][25][26] The use of Perceval sutureless AVR for aortic valve insufficiency does have inherent concerns for possible issues with valve migration, related to the absence of a calcified aortic annulus. 29 The prosthetic valve has been used successfully with modifications to the implant technique and careful assessment of the aortic root anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…5,22 The Perceval sutureless valve (Corcym, Saluggia, Italy) for AVR offers the benefit of short aortic clamp time, excellent hemodynamics, and very low rate of paravalvular leak. 23,24 This is attributed to the complete decalcification of the valve in combination with the nitinol-based frame that secures the device at the annular level. The benefits of the sutureless AVR have not previously been expanded to the biological Bentall (BioBentall) modular construct.…”
Section: Introductionmentioning
confidence: 99%